Resistance of Aedes as a Vectors Potential for Dengue Hemorrhagic Fever (DHF) in Semarang City, Indonesia - Martini Martini; Retno Hestiningsih; Bagoes Widjanarko; Susiana Purwantisasari (Journal of Tropical Life Science, 2019)
Dengue Hemorrhagic Fever (DHF) is a significant health problem in Semarang, Indonesia. A Certain type of insecticides has been widely applied beginning in the last decade as an effort to control the mosquito vectors of dengue virus. This practice could lead to increased resistance in mosquito populations toward these types of insecticides. This research aimed to describe the resistance status of Aedes sp. populations in Semarang. A cross-sectional design study was conducted in 2015, with Aedes sp. populations sampled in several villages of Semarang. Field strains of Aedes sp. eggs were collected using ovitraps and larvae from entomological surveys. Mosquito adults were raised from the collected eggs and larvae under standard conditions and used for biochemical assays. ELISA examined Aedes sp. resistance status. The results showed that there was monooxygenase activity in Aedes sp. populations. In quantitative terms, 77.8% of mosquito samples showed an Optical Density (OD) more than the cut-off point (0.165). Resistance to synthetic pyrethroid insecticide in Aedes sp. mosquitoes population in Semarang may be caused by the mechanism of monooxygenase detoxification enzymes in particular. This case indicated that Aedes sp. has a high capacity as a vector to transmit the dengue virus in Semarang.